Computational Fluid Dynamics (CFD) Analysis of Fuel Sloshing in a Tanker Truck with Different Design of Baffles - Mohd Fauzi, Arif; Mustaffa, Norrizal (Research Progress in Mechanical and Manufacturing Engineering, 2024)
This study presents a comprehensive analysis of the effectiveness of different baffle designs in mitigating fuel sloshing within tanker trucks using computational fluid dynamics (CFD) simulations with ANSYS Fluent. The primary objective was to compare two distinct baffle designs and evaluate their performance across various motion phases: acceleration, constant velocity and deceleration. The results demonstrate that Baffle Design 2 consistently outperforms Baffle Design 1 in controlling fuel movement, reducing turbulence, and minimizing wall shear stress. During the acceleration and deceleration phases, Baffle Design 1 exhibited significant fuel displacement and turbulence, indicating higher instability. In contrast, Baffle Design 2 maintained a more controlled and localized fuel distribution, reflecting superior ability to mitigate fuel movement and reduce sloshing. Force analysis further revealed that Baffle Design 1 experienced higher and more variable forces, suggesting greater instability and dynamic impact on the tank structure. Conversely, Baffle Design 2 exhibited lower and more consistent forces, indicating better control of sloshing and reduced dynamic loads on the tanker. The findings underscore the critical importance of optimized baffle designs in enhancing the safety and durability of tanker trucks. Baffle Design 2’s superior performance in mitigating fuel sloshing not only ensures better fuel stability but also contributes to the overall structural integrity of the tanker. These insights are crucial for designing safer and more efficient fuel transportation systems. The study provides valuable guidelines for future baffle design development aimed at reducing operational risks and improving tanker truck longevity.